Collective excitations and generalized transport coefficients in a molten metallic alloy Li₄Pb - Bryk, T.; Mryglod, I. (Condensed Matter Physics, 2004)
Collective dynamics of a molten metallic alloy Li₄Pb is studied using a combination of analytical multivariable approach of generalized collective modes and molecular dynamics simulations. Dispersion and damping of two branches of propagating collective excitations are analyzed in a wide range of wavenumbers. The features in collective dynamics connected with the large difference in species mass are discussed. Generalized k-dependent transport coefficients for Li₄Pb are reported.